On the brain struggles to recognize basic facial emotions with face masks: an fMRI study - Abutalebi, Jubin; Gallo, Federico; Fedeli, Davide; Houdayer, Elise; Zangrillo, Federica; Emedoli, Daniele; Spina, Alfio; Bellini, Camilla; Del Maschio, Nicola; Iannaccone, Sandro; Alemanno, Federica (Frontiers in Psychology, 2024)
Introduction: The Covid-19 pandemic impacted public health and our lifestyles leading to new social adaptations such as quarantine, social-distancing and facial masks. Face masks, covering extended facial zones, hamper our ability to extract relevant socio-emotional information from others’ faces. In this fMRI study, we investigated how face masks interfere with facial emotion-recognition, focusing on brain responses and connectivity patterns as a function of the presence of a face mask. Methods: 25 healthy participants (13F; mean age: 32.64±7.24y; mean education: 18.28±1.31y) were included. Participants underwent task-related fMRI during the presentation of images of faces expressing basic emotions (joy or fear versus neutral expression). Half of the faces were covered by a face mask. Subjects had to recognize the facial emotion (masked or unmasked). FMRI whole-brain and Regions of Interest analyses were performed, as well as psychophysiological interaction analysis (PPI). Results: Subjects recognized better and faster emotions of unmasked faces. FMRI analyses showed that masked faces induced a stronger activation of a right occipito-temporal cluster, including the Fusiform Gyrus and the Occipital Face Area bilaterally. The same activation pattern was found for the neutral masked > neutral unmasked contrast. PPI analyses of the masked > unmasked contrast showed, in the right Occipital Face Area, a stronger correlation with the left superior frontal gyrus, left precentral gyrus, left superior parietal lobe and the right supramarginal gyrus. Discussion: Our study showed how our brain differentially struggles to recognize face-masked basic emotions, implementing more neural resources to correctly categorize those incomplete facial expressions.